Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1211/0022357011775820
|View full text |Cite
|
Sign up to set email alerts
|

Active intestinal secretion of new quinolone antimicrobials and the partial contribution of P-glycoprotein

Abstract: Transport of quinolone antimicrobials and the contribution of the secretory transporter P-glycoprotein were studied in-vivo and in-vitro. In rat intestinal tissue (Ussing chambers method) and human Caco-2 cells (Transwell method), grepafloxacin showed secretory-directed transport. In both experimental systems, the secretory-directed transport was decreased by ciclosporin A, an inhibitor of P-glycoprotein, and probenecid, an inhibitor of anion transport systems. This suggested the contribution of P-glycoprotein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 13 publications
(15 reference statements)
2
48
0
1
Order By: Relevance
“…Griffiths et al 88 Similar studies by Naruhashi et al 89 demonstrated that grepafloxacin showed secretory-directed transport which was decreased by cyclosporin A, an inhibitor of P-glycoprotein, and probenecid, an inhibitor of anion transport systems. This suggested contributions of P-glycoprotein and anion-sensitive transporter(s).…”
Section: Pharmacokinetics Of New Quinolonesmentioning
confidence: 78%
See 1 more Smart Citation
“…Griffiths et al 88 Similar studies by Naruhashi et al 89 demonstrated that grepafloxacin showed secretory-directed transport which was decreased by cyclosporin A, an inhibitor of P-glycoprotein, and probenecid, an inhibitor of anion transport systems. This suggested contributions of P-glycoprotein and anion-sensitive transporter(s).…”
Section: Pharmacokinetics Of New Quinolonesmentioning
confidence: 78%
“…Moreover, the absorption from an intestinal loop in mdr1a(-/-)/1b(-/-) mice was larger than that in wild-type mice. 89 Accordingly, it appears that some quinolones are transported by secretory transporters, including P-glycoprotein. The involved transporters function in vivo not only to transport grepafloxacin from blood to intestine, but also to limit its intestinal absorption.…”
Section: Pharmacokinetics Of New Quinolonesmentioning
confidence: 99%
“…Plausible candidates for efflux transporters of levofloxacin were P-gp, MRP, and BCRP. [17][18][19] Naruhashi et al reported that the secretory transport of levofloxacin in Caco-2 cells was diminished by a P-gp inhibitor cyclosporin A, a MRP modulator probenecid, and the combination of the two compounds. 17) Yamaguchi et al, however, reported that cyclosporin A and probenecid did not affect the basolateral-to-apical transport of levofloxacin in Caco-2 cells.…”
Section: Transcellular Transport and Membrane Transportmentioning
confidence: 99%
“…[17][18][19] Naruhashi et al reported that the secretory transport of levofloxacin in Caco-2 cells was diminished by a P-gp inhibitor cyclosporin A, a MRP modulator probenecid, and the combination of the two compounds. 17) Yamaguchi et al, however, reported that cyclosporin A and probenecid did not affect the basolateral-to-apical transport of levofloxacin in Caco-2 cells. 18) On the other hand, Xia et al reported that BCRP was expressed at the apical membrane in Caco-2 cells, and transported its substrate, such as estrone-3-sulfate and methotrexate.…”
Section: Transcellular Transport and Membrane Transportmentioning
confidence: 99%
“…P-glycoprotein (ATP-binding cassette B1 (ABCB1)) is known to limit the oral bioavailability of grepafloxacin and salinomycin. [1][2][3] Breast cancer resistance protein (BCRP/ABCG2) affects the oral bioavailability of quinolone antibacterial drugs. 4) P-glycoprotein and BCRP expressed at the brush-border membrane in the intestine work as an absorption barrier of these drugs.…”
mentioning
confidence: 99%